Studying crashes to avoid clashes: A translational approach to develop terminological competence for aeronautic communication - Zhu, Bo; Gao, Hong; Wu, Hexiong; Wang, Wei (Círculo de Lingüística Aplicada a la Comunicación, 2019)
Miscommunication in the cockpit or between pilots and air traffic controllers (ATCs) could be fatal when they use English, the de facto language for international civil aviation. To ensure air safety, the International Civil Aviation Organization (ICAO) has set up English proficiency requirements in Document 9835, calling for adherence to standardized terminology in aeronautic communication. For this reason, terminological competence proves a crucial challenge to non-native speakers of English and merits study from a variety of perspectives. Drawing from relevant work, the current study reports on a translational approach to developing terminological competence for student pilots attending a terminology course tailored to ICAO standards. By extracting subtitles from Mayday, a documentary series on air crashes, near-crashes, and crises, we built a specialized bilingual parallel corpus on aviation and analyzed terminological data against the inventory of events, domains, and sub-domains specified in Document 9835. Through the identification, elaboration, translation, and management of specialized terms, we explore the terminological competence development, and through follow-up interviews we identify the features of this course in shaping student pilots into domain experts qualified for aeronautic communication.